Issues of Labor Organization and Distribution among Inhabitants of Colchis Plain in the Late Bronze – Early Iron Age - Jibladze, Leri (COLLECTION OF SCIENTIFIC WORKS OF SOKHUMI UNIVERSITY, 2025)
The present article discusses the issues connected with organizing the labor arrangement, social division of labor, formation of settlement complexes, channel systems, etc., among the settlers of the Colchis plain in the Late Bronze - Early Iron Age. It is obvious that the organization of labor and public division of labor could not have had a wide character in the Bronze Age as the scale of the settlements was not extensive. This problem is more relevant to the pre-Antique period. Along with other types of settlements in Colchis in the Early Antique period, large unions of Dikhagudzubs had to prepare the ground for formation of the state. Artificially held hill-settlements are sometimes surrounded by 10, 15 and 50 meters wide and 2-3 meters deep canals, the removal of which was led by a clan or community, based on a strict labor organization. In the Early Iron Age, bead-making workshops appeared on the Colchis plain which were based on rich local raw materials. The production made there should not have been intended only for the domestic consumptions, they were export items as well. The facts of discovery of necklaces - making tools and instruments related to the development of that field in that type of settlements, indicate to a large social division - organization of labor and existence of professional artisans.